State Taxes and Reserve Requirements as Major Determinants of Yield Spreads Among Money Market Instruments - Fabozzi, Frank J.; Thurston, Thom B. (Journal of Financial and Quantitative Analysis, 1986)
Frank J. Fabozzi, Thom B. Thurston, State Taxes and Reserve Requirements as Major Determinants of Yield Spreads Among Money Market Instruments, The Journal of Financial and Quantitative Analysis, Vol. 21, No. 4 (Dec., 1986), pp. 427-436